(untitled) (INNOVATIVE ECONOMY, 2025)
Sokhatska O.M., Savitskyі T.V. CHINA’S EXPERIENCE IN INNOVATIVE ENSURING THE COMPETITIVENESS OF ENTERPRISES IN THE GLOBAL MARKET Purpose. The aim of the article is to theoretically summarize the experience of the People’s Republic of China in applying innovative approaches to ensure the competitiveness of enterprises in the global market and to identify on this basis the main success factors that can be adapted by other countries to increase the international competitiveness of their economies, including Ukraine. Methodology of research. The article uses a systematic approach to the analysis of the innovation policy of the PRC, applies methods of logical and structural analysis to identify a multi-level strategy for the implementation of innovations, comparative analysis of international strategies of innovative development to identify new approaches of China, induction method to generalize empirical data on the innovative development of China, as well as analysis of statistical sources of international organizations (OECD, WIPO, World Bank, BloombergNEF, Deloitte) to analytically confirm the effectiveness of innovative development and increase the competitiveness of enterprises of the PRC in the global market. The empirical basis of the study was made up of official documents of the PRC, reports of international organizations and analytical reports. Findings. It was established that China’s innovation breakthrough is based on a multi-level strategy that combines centralized state planning, investments in research and development, large-scale industrial digitalization, and the development of innovation infrastructure. The key mechanisms of state innovation stimulation were identified: the “Made in China 2025” program, the dual circulation strategy, and the creation of science parks and high-tech clusters. The role of university-industry integration and venture capital financing in forming a sustainable innovation environment was emphasized. Originality. A comprehensive model of China’s strategic innovation development was proposed as a system of multi-level integration of science, education, production, and state support. Mechanisms of localization of high-tech production and China’s patent activity were revealed as tools for strengthening national technological sovereignty. The impact of digitalization programs on the growth of productivity and competitiveness of the Chinese economy is substantiated. Practical value. The obtained results can be used in developing national innovation development strategies in other countries, adapting successful Chinese practices to the characteristics of local economies, improving models for supporting startup ecosystems and technology parks, and formulating state policy in the field of digital transformation of industry. Key words: innovative development, China, strategy “Made in China 2025”, digitalization, patent activity, clusters, fiscal policy, “One Belt, One Road”, venture capital, global competition, technological sovereignty.